Los usos del canon europeo en la jurisprudencia del Tribunal Constitucional: una muestra del proceso de armonización europea en materia de derechos fundamentales - Queralt Jiménez, Argelia (Teoría y Realidad Constitucional, 2007)
It is an incontestable fact that domestic judges use the Strasbourg case law as an interpretative tool when applying the Convention or even its own catalogue of rights; however, it is still necessary to establish the real impact of the European jurisprudence. This article seeks to show how the case law of the Spanish Constitutional Court has been influenced by the European canon. With this aim the work exposes the main conclusions achieved through the exhaustive analysis of the Constitutional judgements delivered from 1999 to 2004. This study relies on a proposal of categorisation of the interpretative uses given by the Constitutional Court to the European canon. Each of the categories provides by itself enough evidence of the participation of our Constitutional Court in the harmonization process lead by the Strasbourgh Court in the great Europe.